Speculations in the book of Abu Elfarg Obaid Allah bin Mohammed Almaraghi - Nawaf Hakami (Journal of Umm Al-Qura University for Language Sciences and Literature, 2022)
(Tahthib Aljumal by Alzojaji) or (The book of Sentences) by Abi Alfaraj Obaid Ullah Bin Mohammed Almaraghy is one of the first books dealing with sentences of Alzajjaji. Having studied it for thirty years, the author has provided comments, editing, and simplification. The author as well has reordered the sentences of the book, added, deleted, and reordered some chapters on his own way. The study was on a unique script, where we tried to explore the author's character by introducing him, identifying his grammar school. In the second chapter, we shed light on the chapters of the book by showing the arrangement of the material. The third chapter of our study touched upon the author’s attitude towards gram-mar schools, while the fourth chapter dealt with the author’s attitude towards grammarians. We also have added a chapter on evaluating the book, then we ended the study by presenting the results.